Avaliação do impacto da presença de comorbidades nos desfechos do transplante alogênico de células progenitoras hematopoéticas - Gustavo Machado Teixeira (2014)
Allogeneic hematopoietic stem cell transplantation (AHSCT) is a potentially curative treatment option for many different hematological diseases. Modifications in immunosuppressive therapies, improvements in clinical support care, and the introduction of reduced-intensity regimens (RIC), have led to increasing AHSCT recommendations. Nevertheless, AHSCT continues to have high morbimortality rates, the presence of comorbidities being one of the prognostic factors. The Hematopoietic Cell Transplantationspecific Comorbidity Index (HCT-CI) provided better prediction of transplant related mortality (TRM) in relation to comorbidities. The present study set out to assess the HCT-CI and the Adult Comorbidity Evaluation (ACE-27) as predictors of clinical outcomes post- AHSCT. In the study, we prospectively included adults with malignant or non-malignant hematological diseases, who underwent the first related or unrelated AHSCT and who received hematopoietic stem cells from bone marrow aspiration or peripheral blood. The variables were: HCT-CI, ACE-27 and modified ACE-27 (excluding hematological malignancies), type of primary disease, donor, graft source, conditioning regimen and the use of alemtuzumab. Armands neoplasic disease/disease status index was exclusively assessed in the incidence of relapse. Clinical outcomes included: cumulative incidence of platelet (PR) and granulocyte recovery (GR), sinusoidal obstructive syndrome (SOS), acute and chronic graft versus host disease (GVHD), relapse, transplant-related mortality (TRM), event free survival (EFS) and overall survival (OS). A total 99 patients were assessed and the median age was 38 years (18-65 years), 60.6% were male. HCT-CI 3 corresponded to 8% of cases and hematological malignancies accounted for 75.8% of the recommendations for AHSCT. HCT-CI, ACE-27 and modified ACE-27 were not associated with the AHSCT outcomes. In conclusion, none of the comorbidity indexes assessed influenced the different post-AHSCT outcomes in this population. Factors related to the small sample size could have contributed to these results.